Nanoarchitectonics of metal organic frameworks and PEDOT layer-by-layer electrodes for boosting oxygen reduction reaction. Issue 23 (13th October 2021) - Fenoy, Gonzalo E.; Rafti, Matías; Marmisollé, Waldemar A.; Azzaroni, Omar
Abstract : We present a strategy for the integration of three building blocks in a functional interfacial nanoarchitecture in order to fabricate composite films with improved features towards the electrochemical oxygen reduction reaction (ORR). Abstract : We present a strategy for the integration of three building blocks in a functional interfacial nanoarchitecture in order to fabricate composite films with improved features towards the electrochemical oxygen reduction reaction (ORR). Firstly, multilayer films of polyethyleneimine (PEI) and poly(3, 4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) complex are generated using the layer-by-layer method by making use of the electrostatic interactions between the cationic polyelectrolyte and the negatively charged colloidal polymeric complex. Film assembly shows an exponential growth up to 10 bilayers, with a sharp increase in the amount of deposited material above 4 bilayers. While the electrical connection through the LbL assembled films up to 10 bilayers is efficient, optimal electrochemical performance of the modified electrodes towards the ORR in neutral solutions occurs for 4 bilayers, and then decreases gradually for 6 and 10 bilayers. Subsequently, in order to explore the effect of MOF inclusion on this architecture, Zn-based ZIF-8 nanocrystallites were deposited on the electrodes previously modified with LbL assemblies of 4-bilayers. The micro/mesoporosity, thus added to the films, resulted in an improvement in the ORR performance which can be understood by considering the already demonstrated ability of ZIF-8 for selective oxygen adsorption from solution. Furthermore, ZIF-8 inclusion does not interfere with the ionic transport through the composite film, which is crucial for efficient electrocatalysis. The hereby presented study exemplifies a simple approach for the fabrication and optimization of complex functional interfaces with improved activity towards ORR in neutral pH aqueous environments.